Cyber-Politics: Social Media’s Influence on Political Mobilization - Kharel, Aswasthama Bhakta (Journal of Political Science, 2024)
Commencing with the recognition of social media's profound impact on political mobilisation, this research seeks to conduct an in-depth investigation into the intricate relationship between social media and political engagement, acknowledging the significant influence of digital platforms on civic participation. Employing a methodologically rigorous mixed-methods approach, combining qualitative content analysis and secondary data for quantitative analysis, the study systematically examines the nuanced dynamics of political discourse, information dissemination, and network structures within major social media domains. Guided by Social Movement Theory, the theoretical framework illuminates the instrumental role played by online communities and influencers in shaping contemporary political movements. Preliminary findings emphasize the pivotal contribution of social media to information dissemination, community-building endeavours, and activist initiatives. However, the research also identifies challenges related to misinformation and polarization, highlighting the need for a nuanced understanding of the multifaceted relationship between social media and political engagement. Aligned with a referenced study, this research enhances understanding of the influence exerted by digital spaces on civic engagement, providing a holistic examination of policy discourse, information distribution, and network structures across major social media channels. Establishing a foundation for future research, the study offers pragmatic insights to policymakers, facilitating the discerning utilization of social media platforms for constructive mobilization while mitigating deleterious consequences in the contemporary digital milieu.